"Hot" Issues in Workers' Compensation in Colleges and Universities: Graduate Assistants and Teaching Assistants. (June 2021) - Goonen, Norma M.; Medina-Shore, Sylvia
Workers' compensation laws vary throughout all 50 states and so has the interpretation of those laws regarding whether graduate assistants and teaching assistants should be considered employees for workers' compensation coverage. This review details the history, current situation, key case law, and pros and cons of extending this benefit, whether by the educational institutions themselves or by governmental agencies and courts. The article provides a guide to public and private institutions regarding legal considerations, prevalent practices, and future trends in this continuing controversy.